[OP.6B.04] INDIVIDUAL PATIENT DATA META-ANALYSIS OF SELF-MONITORING OF BLOOD PRESSURE (BP-SMART). (September 2016) - Tucker, K.; Sheppard, J.P.; Stevens, R.; Bosworth, H.B.; Bove, A.; Bray, E.P.; Godwin, M.; Green, B.B.; Hebert, P.; Hobbs, F.D.R.; Kantola, I.; Kerry, S.M.; et al.
Abstract : Objective: Summary meta-analyses suggest that self-monitoring of blood pressure reduces blood pressure in hypertension but important questions remain regarding how best to utilise it and for which groups self-monitoring might be most appropriate. An Individual Patient Data meta-analysis aimed to investigate this further. Design and method: A systematic review captured randomized trials which compared hypertensive patients who self-monitored BP with those who did not. Individual patient data (IPD) were requested from all eligible studies and entered into a 2 stage meta-analysis stratified by trial and adjusting for age, sex, diabetes, baseline BP and intensity of intervention. The primary outcome was change in clinic BP at 12 months. Subgroup analyses assessed the impact of age, sex, baseline BP, baseline treatment and co-morbidities. Results: Of 2, 508 articles in the initial search, 30 trials were eligible, 23 reported the primary outcome. Individual patient data were available from 21 trials, including one unpublished that had not appeared in the search (8, 931 participants). Self-monitoring was associated with reduced clinic systolic blood pressure compared to usual care (−3×3 mmHg, [95% CI −5×0, −1×5 mmHg] at 12 months). Systolic blood pressure reduction and control to target increased with intensity of co-intervention (ranging from no additional support to intensive support). Similar results were seen for diastolic blood pressure. Few data were available after 12 months. Self-monitoring was most effective in those with fewer antihypertensive medications and higher baseline systolic blood pressure up to 170 mmHg but there was no effect in people with previous stroke. Conclusions: Self-monitoring of blood pressure leads to clinically significant blood pressure reduction when combined with more intensive co-interventions including systematic medication titration, education or lifestyle counselling which persists for at least 12 months. People with resistant hypertension or previous stroke may not benefit, perhaps reflecting maximal treatment.